MODEL PEMBERDAYAAN PEREMPUAN MISKIN MELALUI PROGRAM KEUANGAN MIKRO SYARIAH BERBASIS MASYARAKAT (PROGRAM MISYKAT DPU-DT) - Arif Pujiyono (Jurnal Ekonomi & Keuangan Islam, 2011)
Poverty is a problem that caused the failure of economic systems. Women have great potential in helping to overcome poverty. Indonesia has great potential to optimize the social fund an independent source of Zakat, and alms infak (ZIS) through empowerment of the poor. This research is to analyze financial assistance to community-based micro-sharia (Misykat) DPU-DT in Central Java. The results showed that the program can improve that Misykat welfare poor women. Wilcoxon different test results Misykat program can increase consumption, income, profits and savings of poor women beneficiaries Misykat. Additionally, the program Misykat increasing empowerment of poor women, shoft their skill level increases based on the size of confidence, business skills, business success and the science of religion.Â